Automatic Neonatal Seizure Detection by EEG - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
EEGs obtained from 55 newborns, recorded at the Montreal, Sydney, and Texas Children's Hospitals, were reviewed by 3 types of automatic analysis of sequential epochs aimed at detecting rhythmic paroxysmal discharges, repetitive spike patterns, arrhythmic runs of spikes, and low frequency discharges, and the methods are reported from the Montreal Neurological Institute, and the Montreal Children's Hospital, Canada.